2018
DOI: 10.3390/ijgi7100405
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-2 Based Temporal Detection of Agricultural Land Use Anomalies in Support of Common Agricultural Policy Monitoring

Abstract: The European Common Agricultural Policy (CAP) post-2020 timeframe reform will reshape the agriculture land use control procedures from a selected risk fields-based approach into an all-inclusive one. The reform fosters the use of Sentinel data with the objective of enabling greater transparency and comparability of CAP results in different Member States. In this paper, we investigate the analysis of a time series approach using Sentinel-2 images and the suitability of the BFAST (Breaks for Additive Season and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
0
25
0
3
Order By: Relevance
“…For instance, Schmedtmann and Campagnolo [24] proposed a reliable crop identification (12 classes, OA = 68%) over Portuguese parcels covering 1057 km 2 , Sitokonstantinou et al [25] developed a parcel-based crop identification (nine classes, OA = 91.3% and k = 0.87) scheme for CAP and greening obligations over a Spanish area of 215 km 2 . Kanjir et al [48] developed a change detection method to support land use control within CAP activities over three areas of 7 km 2 in Slovenia, and Blaes et al [23] developed a framework for area-based subsidies control in Belgium. The present study reported overall accuracy reaching ≈ 94%, which is similar to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Schmedtmann and Campagnolo [24] proposed a reliable crop identification (12 classes, OA = 68%) over Portuguese parcels covering 1057 km 2 , Sitokonstantinou et al [25] developed a parcel-based crop identification (nine classes, OA = 91.3% and k = 0.87) scheme for CAP and greening obligations over a Spanish area of 215 km 2 . Kanjir et al [48] developed a change detection method to support land use control within CAP activities over three areas of 7 km 2 in Slovenia, and Blaes et al [23] developed a framework for area-based subsidies control in Belgium. The present study reported overall accuracy reaching ≈ 94%, which is similar to the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sentinel-2 holds great potential for assisting the crop type inspections and there are numerous methods available for various different agricultural applications [10], but still no common workflow, method, or tool that can be easily adopted by the PAs. The DiAS DSS prototype complements current efforts in this direction from the Sen2-Agri project [16], the RECAP project [17,18], and the Sen4CAP [19], by providing a simple workflow through an easily operated tool, with instructions that were developed in a participatory approach.…”
Section: Discussionmentioning
confidence: 99%
“…The RECAP project aims to provide on one hand, information to authorities and agricultural consultants, and on the other hand, assists farmers' decisions according to CAP regulations and prerequisites [17,18]. The Sen4CAP project attempts to incorporate Sentinel data in order to support the aims of modernizing the new CAP post-2020 by focusing in developing advanced algorithms and effective workflows [19]. However, the operational capacity of the proposed workflows of these projects have not been fully assessed and in recognition of the complexity of the problem, the discussions of PAs have not yet reached to a conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…A second, less prescriptive, approach is to support eco-agriculture [72] or ecological intensification [73] , which creates local diversity through the redesign of the farming system [54] . Finally the policy must be monitored, addressing the range of core indicators, using remote sensing [74] and/or surveys [43] .…”
Section: Manage the Systemmentioning
confidence: 99%